BIMBINGAN ADAB SANTRI MELALUI KAJIAN KITAB AKHLAQ LI AL-BANIN JUZ 1 PADA SANTRI PUTRA PONDOK PESANTREN DARUSSHOLAH GUMIRIH SINGOJURUH BANYUWANGI - Masnida Masnida; Izzah Nabila Fauzi (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2023)
Good behavior or adab towards teachers is the main goal when the process of seeking knowledge must be carried out by every santri. As for the purpose of this research is to find out the application of adab material in the book of morals Li al-Banin. In this study, the type of research used is qualitative research. Santri as research objects are used as a means to obtain data. The way to obtain the data is done by the method of observation, interviews and documentation. The data obtained were analyzed to obtain answers according to the research theme. In this study, the type of research used is qualitative research. Santri as research objects are used as a means to obtain data. The way to obtain the data is done by the method of observation, interviews and documentation. The data obtained were analyzed to obtain answers according to the research theme. The results of this study are used as input for the students to improve manners when seeking knowledge which has been mentioned by Shaykh Umar bin Ahmad Baradja in the Book of Akhlaq Li al-Banin Juz 1 in order to get the essence of knowledge when seeking knowledge.